Prognostic significance of surfactant protein A, surfactant protein D, Clara cell protein 16, S100 protein, trefoil factor 3, and prostatic secretory protein 94 in idiopathic pulmonary fibrosis, sarcoidosis, and chronic pulmonary obstructive disease - Doubková, Martina; Karpíšek, Michal; Mazoch, Jiri; Skřičková, Jana; Doubek, Michael (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Identification of serum and bronchoalveolar lavage fluid (BALF) biomarkers may facilitate diagnosis and prognostication in various lung disorders. Objective: Serum and BALF levels of surfactant protein A (SP-A), surfactant protein D (SP-D), Clara cell protein 16 (CC16), S100 protein, trefoil factor 3 (TFF3), and prostatic secretory protein 94 (PSP94) were evaluated in 94 consecutive patients (idiopathic pulmonary fibrosis (IPF; n=18), sarcoidosis (n=25), chronic obstructive pulmonary disease (COPD; n=51)), and in 155 healthy controls. Methods: Biomarkers were measured at diagnosis and compared with disease characteristics. Both uniparametric and multiparametric analyses were used. Results: Seven significant correlations were found: 1) BALF PSP94 level correlated with prognosis of sarcoidosis (P=0.035); 2) BALF SP-D level with pulmonary functions in IPF (P=0.032); 3) BALF SP-D and TFF3 with IPF mortality (P=0.049 and 0.017, respectively); 4) serum TFF3 level with COPD mortality (P=0.006,); 5) serum SP-A with pulmonary functions impairment in IPF (P=0.011); 6) serum SP-D level was associated with HRCT interstitial score in IPF (P=0.0346); and 7) serum SP-A was associated with staging of COPD according to spirometry (P